The Discovery of an American Brig: Fieldwork Involving Applied Remote Viewing Including a Comparison with Electronic Remote Sensing - Schwartz, Stephan Andrew (Journal of Scientific Exploration, 2020)
In the fall of 1987 Mobius began fieldwork, under a license from the Bahamian Government, to carry out an archaeological survey in an area of the Grand Bahama Banks encompassing some 579.15 square miles (1500 sq. km). This report compares the Remote Viewing, electronic remote sensing, and visual search process used to locate the wreck site of a previously undiscovered armed American merchantman believed to be the Brig Leander, which was found in a sub-section of the License Area known as Consensus Zone C; an area of 11.81 sq. miles (30.59 sq. km) of water. It concludes that Remote Viewing was the source of information which led to the site’s location, and that electronic remote sensing was not useful in this instance. Leander was under the Command of Captain William Johnson when she sank for unknown reasons near Beaks Cay on 6 April 1834, while returning from Manzanilla, Cuba to her homeport in Boston, Massachusetts. In addition to location information, a total of 193 conceptual descriptive concepts concerning the site were proffered by twelve Remote Viewers. Of this, 148 concepts, or 75% of the total, could be evaluated through direct field observations, or historical research. An evaluation of this material reveals 84% Correct, 12% Partially Correct, 4% Incorrect. There is little accuracy variation across the sequence of material from the Los Angeles interviews (84% Corr., 13% Part. Co rr. ,3% Incorr.), to the on-site data (81% Corr., 11% Part. Corr., 8% Incorr.). Approximately 300 notable wrecks went down, not just in the License Area but across the entire Banks, from 1500 to 1876 as determined by a thorough search of historical records and archival material in the U.S., the U.K., Spain and the Bahamas. To make a conservative assessment of this location occurring by chance, assume the wrecks are evenly distributed not throughout the Banks, but only within the License Area. That said, we should expect to see 6.12 boats in Consensus Zone C (11.81/579.15 x 300 =6.12). The brig site is 5000 square feet (464.5 sq. m), equaling 0.00018 of a square mile. Within Consensus Zone C 65,849 sites of this size could be placed, thus yielding a grid of 65,849 cells.. If the probability of selecting this particular cell in the grid by chance exceeds p≥ 0.05 then Remote Viewing can be considered a determinative factor. The probability of finding this one 5,000 square feet area is then 6.12/65,849 = p 0.00009, which strongly suggests that chance is not an explanation for the location of Leander. History: “The Discovery of an American Brig: Fieldwork Involving Applied Archaeological Remote Viewing,” Parapsychological Association Conference 1988. Also, The Discovery of an American Brig: Fieldwork Involving Applied Archaeological Remote Viewing, Including a Comparison with Electronic Remote Sensing,” Conference on Underwater Archaeology/Society of Historic Archaeology Annual Meetings. 1989.